Logit and Complementary Log-Log Modeling in the Case of Factors Affecting Heart Failure Disease - IGA MAWARNI; Asyifa Dwi Ayshah; Dhiyaa Fitri Yafe; Fadhilah Fitri (UNP Journal of Statistics and Data Science, 2025)
Heart failure is one of the leading causes of morbidity and mortality globally. Heart disease is a disease caused by plaque that builds up in the coronary arteries that supply oxygen to the heart muscle. Research on heart failure disease aims to find out what factors affect heart failure disease and how much influence it has. This test was conducted using logistic regression method with logit modeling and complementary log-log modeling in analyzing data of 918 patients with heart failure disease. This study also takes which modeling is the best. The results of this analysis indicate that Age, Gender, Blood Sugar, and Chest Pain have significant effects on the likelihood of Heart Failure. Specifically, higher blood sugar levels and the presence of chest pain were found to increase the probability of heart failure, while gender and age showed varying effects across different age groups. Based on the model comparison, the Logit model demonstrated better fit and predictive accuracy than the Complementary Log-Log model, as reflected by its lower AIC value 897.43.